Framing the Author Surrogate for an Academic Docufiction Screenplay - Patrick, Nicodemus Adai; Rantimi, Julius-Adeoye; Babarinde, Damilola; Badeji, Susan Olubukola (Corpus Intellectual, 2024)
This paper explores the relationship between fiction and reality in the docufiction genre, concentrating on the function of the author's surrogate characters. Docufiction is a hybrid genre that combines fiction and documentary elements, providing filmmakers with a distinctive medium to cinematically express their viewpoints on actual events. However, the emergence of “academic screenwriting” from academia presents an alternative practice that sees the screenplay not just as a blueprint that depends on an audio/visual production for its consumption but as both a method of research enquiry and an independent research artefact which generates and disseminates new knowledge and most importantly new ways of practice. In this context, it is crucial to investigate the framing of the author's surrogates in an academic screenplay meant to be read since these characters work as a means of purposefully blurring the lines between the author's voice and the reality that is portrayed. The study deployed qualitative in gathering data. Content analysis was used in analyzing the content of “The 37th State”, an academic docufiction feature screenplay written as part of ongoing Practice-Based research in screenwriting. Secondary data were collected through books, journals, archival documents and online sources. Postmodern character theory was used in analyzing the author surrogate hybrid characters in “The 37th State”, with keen interest on how they are constructed and smoothly incorporated into the narrative through framing and identifying the roles they play such as navigating the narrative, serving as interviewers and documentarians, representing the author's experience (s) and reflecting the author’s values. The study found that by intentionally blending facts and fiction through this character, authors can create narratives that reflect their perspectives on actual events and challenge conventional ideas about truth and imagination.